Application of low-cost tools and techniques for landslide monitoring - Eyo, E. (Springer International Publishing, 2014)
This paper proposes a low-cost landslide monitoring system using the Reverse Real-Time Kinematic (RRTK) technique. The server-based processing technique, which utilizes the two-way communication channel for the computation and transmission of the user’s accurate position, is discussed. The basic infrastructure requirements for RRTK in lowcost landslide monitoring application are described. In order to implement the proposed RRTK algorithm, real-time data streaming of raw Global Positioning System (GPS) data of both the reference and rover station(s) to the control centre, are performed. A high pass filtering technique was employed to detect outliers in the observations. Finally, the autocorrelation of GPS time series was investigated to validate the presence of white and coloured noises in the GPS observations.